Creatina aumenta a atividade da Na+,K+-ATPase e previne o aparecimento das convulsões induzidas por pentilenotetrazol em ratos - Rambo, Leonardo Magno (2010)
Creatine, an endogenous guanidino compound produced on liver, kidneys, pancreas, testes and brain, has been aim of several studies over the last years. Although most studies attribute the effects of creatine to their energetic buffer role, recent findings have suggested actions non-related to energy metabolism. Researches have shown that this compound may act as a neuromodulator in the central nervous system (CNS). Among these neuromodulatory actions, was demonstrated that creatine modulates NMDA receptors in rat hippocampal slices. It is well know that stimulation of these receptors activates Na+,K+-ATPase. Moreover, little is known about the acute role of this compound on CNS. Thus, the objective of the chapter I of this paper was to investigate the effect of creatine on Na+,K+-ATPase activity and the intracellular signaling pathway involved. The results showed that creatine treatment of rat hippocampal slices increased Na+,K+-ATPase α2/3 activity in vitro. The intracerebroventricular administration of this compound also increased the enzyme activity, ex vivo. Furthermore, creatinine and phosphocreatine treatment of hippocampal slices did not alter the enzyme activity, suggesting that the creatine mechanism of action is independent of energy metabolism. Additionally, we showed the involvement of NMDA-NR2B and calcineurin. We found also the involvement of the PKA and PKC in the effect of creatine on Na+,K+-ATPase activity. In the second chapter of this study, we decide to verify the effect of acute creatine administration on PTZ-induced seizures, since this convulsant agent inhibits Na+,K+-ATPase activity without alter bioenergetic cellular state. We found that creatine treatment protected against behavioral and electroencephalographic seizures induced by PTZ. Moreover, creatine acute treatment prevented PTZ-induced inhibition of Na+,K+-ATPase activity. Based on present findings, we suggest that creatine may act through an alternative mechanism, independent of energetic metabolism, by modulation of Na+,K+-ATPase activity.